Zulu warriors : the battle for the South African frontier - Laband, John, 1947- (Yale University Press, 2014)
"The Anglo-Zulu War, the most famous of Britain's lte ninetweenth-century campaigns of colonial conquest, was not fought in isolation. Along with the two Anglo-Pedi wars, the Ninth Cape Frontier War and the Northern Border War, it was one in a brutal series of interconnected and overlapping wars which the British waged between 1877-1879 to crush and disarm the remaining independent black states of South Africa. [Fusing] the widely differing African and European perspectives on events, [the author] probes the fateful decisions taken by statesmen and military commandrs, analyses military operations and their destructive impact on combatants and civilians alike, and explores why so many Africans chose to fight as auxiliaries and levies alongside the Bruitish instead of against them. ..."--Jacket.